Calcium Phosphate Ceramics Can Prevent Bisphosphonate-Related Osteonecrosis of the Jaw - Paulo, Siri (2020)
Bisphosphonate-associated osteonecrosis of the jaw (BRONJ), a post-surgical non-healing wound condition, is one of the most common side effects in patients treated with nitrogen-containing bisphosphonates. Its physiopathology has been related with suppression of bone turnover, of soft tissue healing and infection. Biphasic calcium phosphates (BCP) are used as a drug delivery vehicle and as a bone substitute in surgical wounds. Due to their capacity to adsorb zoledronate, it was hypothesized these compounds might have a protective effect on the soft tissues in BRONJ wounds. To address this hypothesis, a reproducible in vivo model of BRONJ in Wistar rats was used. This model directly relates chronic bisphosphonate administration with the development of osteonecrosis of the jaw after tooth extraction. BCP granules were placed in the alveolus immediately after tooth extraction in the test group. The animals were evaluated through nuclear medicine, radiology, macroscopic observation, and histologic analysis. Encouragingly, calcium phosphate ceramics were able to limit zoledronate toxicity in vivo and to favor healing, which was evidenced by medical imaging (nuclear medicine and radiology), macroscopically, and through histology. The studied therapeutic option presented itself as a potential solution to prevent the development of maxillary osteonecrosis.